Efek Ekstrak Etanol Kayu Manis (Cinnamomum burmannii) terhadap Kadar MDA Ginjal pada Tikus Wistar Hiperglikemi (The Effect of Cinnamon (Cinnamomum burmannii) Ethanolic Extract on Kidney MDA in Hyperglycemic Wistar Rats) - Vidya Muqsita; Elly Nurus Sakinah; Ali Santosa (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Cinnamon contains natural antioxidant polyphenols. Polyphenols reduces lipid peroxidation by lowering levels of MDA. This study aimed to prove the effect of ethanolic extract of cinnamon (Cinnamomum burmannii) on decreasing kidney MDA levels of rat. This research was true experimental post-test only control group design. Twenty five rats 2-3 months of age, were divided into 5 groups: K(-) without alloxan induction, K(+) was induced with alloxan 100 mg/kg, group P1, P2, and P3 were induced with alloxan 100 mg/kg and cinnamon ethanolic extract 200 mg/kg, 400 mg/kg and 600 mg/kg, respectively for 7 days. At the end of the treatment, MDA concentration of kidney was measured by using ELISA method. The average of kidney MDA level were K(-), K(+), P1, P2, and P3 grups were 1.8923 ng/g, 1.8926 ng/g, 1.8926 ng/g, 1.8925 ng/g, and 1.8926 ng/g, respectively. Data was analysed using One Way ANOVA, and resulted p = 0.238. The conclusion was cinnamon ethanolic extract could not reduce kidney MDA levels in hyperglycemic wistar rat induced with alloxan. Keywords: Cinnamomum burmannii, polyphenols, alloxan, MDA